The impact of nursing students on the health-related quality of life and perceived social support of a rural population in Ecuador: effects of a service-based learning course - Rebecca L. Walcott; Angela M. Murcia; Gloria M. Berry; Christian F. Juna; María Isabel Roldós; Phaedra S. Corso (BMC, 2018)
Abstract Background Students seeking degrees in healthcare in Ecuador participate in community improvement projects and provide free health services under the supervision of faculty health professionals. The aim of this study is to determine the impact of a community-based intervention delivered by nursing students on health-related quality of life (HRQoL) and perceived social support of a rural population in Ecuador. Methods A quasi-experimental non-equivalent control group design study was conducted in two rural communities in Tumbaco, Ecuador. Families from one rural community were invited to participate in the intervention, receiving 8 weekly home visits from nursing students. Families from a neighboring community were similarly recruited as wait-list controls. One member of each family was consented into the study; the final sample included 43 intervention participants and 55 control participants. HRQoL and perceived social support were assessed before and after the intervention in both groups. The SF-12 was used to measure HRQoL, including eight domain scores and two composite scores, and the Interpersonal Support Evaluation List was used as an indicator of perceived social support. Difference-in-differences (DD) analyses were conducted to mitigate the effects of any baseline differences in the non- equivalent control group design. Results When compared to the control group, the intervention group realized significant improvements in the physical component summary score of the SF-12 (4.20, p < 0.05) and the physical function domain of the SF-12 (4.92, p < 0.05). There were no statistically significant differences for any other components of the SF-12 or in the measure of perceived social support. Conclusions Nursing students completing their rural service rotation have the potential to improve the health-related quality of life of rural residents in Ecuador. Future research should continue to examine the impact of service-based learning on recipient populations.